The worst person in the world - Fløttum, Ola 1972- (<<The>> Criterion Collection, 2022)
"Renate Reinsve won the Best Actress prize at Cannes for the revelatory, complex performance that anchors this sprawlingly novelistic film by Norwegian auteur Joachim Trier, an emotionally intricate and exhilarating character study of a woman entering her thirties. Amid the seemingly endless possibilities of the modern world, Julie (Reinsve) wavers over artistic passions and professions, the question of motherhood, and relationships with two very different men: a successful comic-book artist (Trier regular Anders Danielsen Lie) and a charismatic barista (Herbert Nordrum). Working with a team of longtime collaborators, Trier and his perennial cowriter Eskil Vogt construct in The Worst Person in the World, the Oscar-nominated third entry in their unofficial Oslo Trilogy, a liberating portrait of self-discovery and a bracingly contemporary spin on the romantic comedy." [filmdienst-de]
Original: Norwegen, Frankreich, Schweden, Dänemark 2021
Director-approved DVD special edition features: new 2K digital master ; new interviews with director Joachim Trier; coscreenwriter Eskil Vogt; actors Renate Reinsve, Anders Danielsen Lie, and Herbert Nordrum; cinematographer Kasper Tuxen; and sound designer Gisle Tveito ; on-location footage from the creation of the film's time-freezing footage ; deleted scenes ; plus: an essay by Sheila O'Malley
Bildformat 1.85:1
Keywords: Film; DVD-Video